Organic Pigment from Cassava Peel as Intermediate Material Marker Ink - Martomo Setyawan; Suci Fazriyah N; Lara Arilisa K (Indonesian Journal of Chemical Engineering, 2023)
Cassava is the third staple food after rice and corn, and it’s production increase every year. Cassava production for food produces waste in the form of carbon-containing peel. It is known that carbon is used as the main ingredient in the paint and ink manufacturing industry. Carbon from cassava husk can be used as organic ink that is environmentally friendly and safe for health by using natural resins in the form of arabic gum, alcohol, and Polyetilen Glikol solvents which are processed through the stages of water content reduction, carbonization in furnance, purification and variation based on the mass of arabic gum and stirring speed. The color of the ink produced will be more concentrated if the amount of gum arab mass used more and more. The stirring speed will also make the light intensity will be higher